Model Pemisahan (Spin-Off) Unit Simpan Pinjam Menjadi Koperasi Simpan Pinjam yang Independen - Sugiyanto Sugiyanto; Mutiara Nur Azizah (LPPM Universitas Koperasi Indonesia, 2026)
This study aims to formulate a spin-off model for Savings and Loan Units (USP) into independent Savings and Loan Cooperatives (KSP), as mandated by the Regulation of the Minister of Cooperatives and SMEs of the Republic of Indonesia Number 8 of 2023. The study uses a qualitative case study approach, data were collected through interviews and document analysis at the Bandung City Government Employees Cooperative (KPKB), whose USP assets exceed 50% of the cooperative's total assets. The study findings indicate that a successful spin-off requires comprehensive preparation in several key aspects: institutional and legal compliance, organizational restructuring, membership separation, asset and capital division, human resource readiness, and operational infrastructure. Based on these considerations, the study proposes a multi-stage spin-off model that includes: (1) member approval through the Annual Members Meeting (RAT), (2) preparation of a legal deed, (3) registration through the Online Single Submission (OSS) system, and (4) establishment of an independent KSP governance structure. The main challenges identified include regulatory complexity, administrative readiness, member acceptance, and initial operational costs. Conversely, spin-offs offer significant opportunities to improve financial transparency and accountability, service focus, and long-term business sustainability. This model provides practical guidance for cooperatives undergoing similar mandatory transitions and contributes to the evolving literature on cooperative restructuring and compliance with financial sector regulations.